ANALISIS ALOKASI ANGGARAN DALAM PENGELOLAAN TAMAN NASIONAL WAY KAMBAS - Winahyu Adyananda Putri; Tutut Sunarminto; Rinekso Soekmadi (Media Konservasi, 2014)
Way Kambas National Park (TNWK) is one of conservation area which has high potential of diversity and ecotourism. Several arrangements applied to accomplish goal of TNWK management. One important thing that must be considered in development is money management. Purpose of this research are to analyze budgeting mechanism, score realization of activity and budget in TNWK management, and also analyze the effectivity of budgeting system in TNWK. Result showed that TNWK got the most money resource from government.. Mechanism budgeting in TNWK dominated by TNWK central office, section and resort had not yet taken important role in mechanism. Base on Likert Scoring, TNWK management almost suit according to good management principal. Activities and budget which implement could solve several problems in TNWK, but it’s still have not enough to optimize the management.  Most of TNWK budget was used for technical support. The proportion of the budget had an impact to the limited budget allocation for the basic activities in achieving effectiveness management and accomplish goal of TNWK. Based on conservation value, most of the budget was allocated to the protection and preservation aspect.   Keywords: Activities and programs, Budgeting, Conservation, Management, Way Kambas National Park.